A direct link of the Mos-MAPK pathway to Erp1/Emi2 in meiotic arrest of Xenopus laevis eggs - Inoue, Daigo; Ohe, Munemichi; Sagata, Noriyuki (Nature, 2007)
In vertebrates, unfertilized eggs (or mature oocytes) are arrested at metaphase of meiosis II by a cytoplasmic activity called cytostatic factor (CSF). The classical Mos-MAPK pathway has long been implicated in CSF arrest of vertebrate eggs, but exactly how it exerts CSF activity remains unclear. Recently, Erp1 (also called Emi2), an inhibitor of the anaphase-promoting complex/cyclosome (APC/C) required for degradation of the mitotic regulator cyclin B (ref. 5), has also been shown to be a component of CSF in both Xenopus and mice. Erp1 is destroyed on fertilization or egg activation, like Mos. However, despite these similarities the Mos-MAPK (mitogen-activated protein kinase) pathway and Erp1 are thought to act rather independently in CSF arrest. Here, we show that p90rsk, the kinase immediately downstream from Mos-MAPK, directly targets Erp1 for CSF arrest in Xenopus oocytes. Erp1 is synthesized immediately after meiosis I, and the Mos-MAPK pathway or p90rsk is essential for CSF arrest by Erp1. p90rsk can directly phosphorylate Erp1 on Ser 335/Thr 336 both in vivo and in vitro, and upregulates both Erp1 stability and activity. Erp1 is also present in early embryos, but has little CSF activity owing, at least in part, to the absence of p90rsk activity. These results clarify the direct link of the classical Mos-MAPK pathway to Erp1 in meiotic arrest of vertebrate oocytes.